Synergy of Government and Community Participation in Regional Development: A Study of Bandar Lampung - Adam Mulya Adi Wijaya; Erlin Kurniati (DPPM Universitas Pelita Bangsa, 2025)
The role of the government and the involvement of the community are crucial for regional development. In Bandar Lampung, the local government has initiated several infrastructure projects aimed at improving the city’s urban landscape. However, the level of community participation in the planning and implementation of development programs remains suboptimal. This study examines the dynamics of government and community collaboration in regional development in Bandar Lampung. The research employed a qualitative method through interviews, observations, and document analysis to gain an in-depth understanding of stakeholder perspectives. The findings suggest that while government-led development programs are progressing, there is a significant gap between policy implementation and community engagement. Furthermore, challenges such as uneven infrastructure distribution, limited community awareness, and inadequate participatory mechanisms need to be addressed to ensure more inclusive and equitable development. This research contributes academically by providing empirical insights into participatory governance practices at the local level, while practically offering recommendations for strengthening community engagement frameworks in regional development. The findings can inform policymakers in designing more responsive and participatory development strategies in Bandar Lampung and similar urban settings.